Pengaruh Faktor Internal dan Eksternal Terhadap Harga Saham - Yudistira, Elvin Ruswanda; Adiputra, I Made Pradana (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
The purpose of this experiment is to prove internal factors and external factors to the stock price. Internal factors include: Return on Assets, Return on Equity, Net Interest Margin and Operating Costs / Operational Scoping. While external factors include: the inflation rate and the BI rate. The population in this study is the company placed on the Indonesia Stock Exchange (IDX) in the banking sector for the 2015-2019 period. There were 32 people represented in this study and used a collection technique, namely purposive sampling. The final results in this study indicate that ROA has a positive and significant effect on stock prices. ROE is negative and significant towards stock prices. Negative shares and insignificant stock prices. BOPO negative and insignificant influence on stock prices. The inflation rate is negative and insignificant towards stock prices. BI Rate has a positive and insignificant effect on stock prices. Simultaneously ROA, ROE, NIM, BOPO, Inflation Rate and BI Rate significantly influence stock prices.